A Comparison of Non Blind Image Watermarking Using Transformation Domain - Kartikadarma, Etika; Udayanti, Erika Devi; Sari, Christy Atika; Doheir, Mohamed (Scientific Journal of Informatics, 2021)
Purpose: This study aims to know which of the algorithms had the better results for image processing by comparing these two algorithms for blind watermarking as the prevention of image plagiarism. Methods: The DCT and HWT algorithms used to get better results. Result: The results of this study indicate that HWT has better results for image processing, especially blind watermarking because the results with MSE, PSNR, and NC show that HWT has advantages in every aspect.  using 512x512 pixels grayscale image as cover image, the MSE result from HWT is 0.0004156 with PSNR 81.9440 better than MSE from DCT 0.003 with PSNR 73.2949. Novelty: Robustness aspect has been tested using NC. DCT has good NC than HWT only in JPEG compression attack with value is 1, while another attack has better NC in HWT that yield close to 1.